Occurrence of a resveratrol trimer diglucoside derivative with a fused heptacyclic skeleton in Shorea uliginosa. (June 2022) - Ito, Tetsuro; Nishiguchi, Masataka; Fukaya, Masashi; Ryu, Kaori; Iinuma, Munekazu
Abstract: Uliginoside H (1 ) is a new resveratrol trimer diglucoside derivative with fused heptacycles. It was discovered from the acetone extract of the stem bark of Shorea uliginosa (Dipterocarpaceae). Spectroscopic analysis, such as NMR experiments, was used to elucidate the structure, and the absolute configuration was determined using circular dichroism data. Notably, 1 has a fused ring system composed of a dihydrobenzofuran ring, a hexahydrocyclopenta[ c ]chromene ring, and a cyclohex-2-enone ring, each with eight asymmetric carbons. Thus, a plausible biosynthetic pathway for 1 was proposed. Graphical Abstract: ga1 Highlights: Uliginoside H is a C -di-glucoside of trimeric resveratrol. Uliginoside H is isolated from Shorea uliginosa . Absolute configuration was determined based on NMR and CD spectral properties. Structure of the core heterocyclic skeleton bearing dearomatized ring was elucidated. The plausible biosynthetic pathway was proposed.